2022
DOI: 10.1007/s00431-022-04504-w
|View full text |Cite
|
Sign up to set email alerts
|

Medicine and supplement use in infants, children, and adolescents depends on sex, age, and socioeconomic status: results of a German longitudinal population-based cohort study (LIFE Child)

Abstract: Children and adolescents are exposed to medicines and supplements, but only a few studies have evaluated the actual intake in routine care. Thus, we performed a pharmacoepidemiological evaluation of a longitudinal population-based pediatric cohort study (LIFE Child) conducted at the University Hospital of Leipzig between 2014 and 2019. We analyzed all visits of the participants of the LIFE Child cohort between 1 January 2014 and 31 December 2019. Participants were asked to bring their medicines and supplements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The use of dietary supplements is currently increasing also in many European countries [ 18 , 19 , 20 ]. Recent data also suggest that the use of supplements is particularly elevated in families with a high socioeconomic status [ 21 ]. A preliminary analysis of Google Trend data by the authors of this paper shows that the number of searches by consumers on multivitamin products in Italy, Switzerland, Germany, France, the United Kingdom, and the United States has tripled over the past 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…The use of dietary supplements is currently increasing also in many European countries [ 18 , 19 , 20 ]. Recent data also suggest that the use of supplements is particularly elevated in families with a high socioeconomic status [ 21 ]. A preliminary analysis of Google Trend data by the authors of this paper shows that the number of searches by consumers on multivitamin products in Italy, Switzerland, Germany, France, the United Kingdom, and the United States has tripled over the past 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Written informed consent was obtained from participating adolescents and their parents. More information about the study design, data collection, and other details has been published previously [25,26,28].…”
Section: Methodsmentioning
confidence: 99%
“…The authors also observed that Canadian children whose parents completed education up to college level (vs. secondary school education or less) and those living in metropolitan areas (vs. rural) were significantly more likely to take vitamin D supplements. In the study carried out by Herzig et al (2022) the intake of supplements, including calcium and vitamin D, was more prevalent in German participants with a higher SES compared to those with a lower SES. In China, the use of calcium supplements was very common among supplement users (58.5% of children between 0 and 5 years old), particularly in higher income households, and about half of the children taking calcium supplements were also taking vitamin D (Chen et al, 2014).…”
mentioning
confidence: 99%